(untitled) (Scientific journal of the Fergana State University, 2024)
This article reveals about the emir, who was sentenced to emigrate from the Emirate of Bukhara, the beks, officials who moved with him to a neighboring state, representatives of the common people such as dehkans, pastoralists, artisans, workers who unknowingly followed the emir, the leaders of the "Basmachi" gangs fighting against the Soviet regime and the defeated, as well as their troops, about the fate of the rich, who lost their farms as a result of land and water reform, political emigrants who acted as part of the government of the BSSR, and then joined the ranks of the national opposition